El Camino a Santiago: andares y devociones de un peregrino del siglo XII según el Liber Peregrinationis - Ruiz Montejo, Inés (Revista de Filología Románica, 2006)
Codex Calistinus’ 5th book, called «Liber Peregrinationis» or «Pilgrim’s Guide», written by Aymeric Picaud after his travel to Compostela between 1130 and 1140, captures the environment around Santiago’s worship clearly. It shows the conditions of the Road to Compostela, gives moral advice, claims the most respect and the best received for the pilgrim, and, above all, it praises the Apostle’s Cathedral as the most glorious holy dwelling.